Perancangan Websıte Rebrandıng Bersama Rıztour Terhadap Kulıner dı Batam - Jimmy Pratama; Wendy Aprianto (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
PT. Riztour Indo Wisata is a business engaged in tourism which was founded in 2014, located at Ruko Shangrila Garden Blok A No. 18, Sekupang. The obstacles faced by PT. Riztour Indo Wisata while running its business activities in the form of the absence of a culinary website system that functions as a promotional tool to increase tourists who want to travel to the city of Batam. The methodology applied in this research is applied research that aims to solve problems in the modern world. The method used in this activity is SDLC (System Development Life Cycle) method which has 5 stages, namely requirement analysis, design, development, testing, maintenance. The tools are hosting, domain, wordpress, and page builder from elementor. The output of this research is in the form of a culinary website system that contains information about restaurants, recipes, typical food of the city of Batam. With this system, tourists PT. Riztour Indo Wisata makes it easier and faster to find information about culinary in the city of Batam